A reimagined world: international tertiary dance education in light of COVID-19. Issue 3 (2nd September 2021) - Heyang, Tuomeiciren; Martin, Rose
ABSTRACT: Coronavirus disease (COVID-19) is currently sweeping the globe. With this pandemic impacting social, political and economic spheres, this article unpacks COVID-19 in relation to international tertiary dance education, asking: How are we sustaining international relationships and global dialogues within dance education in light of COVID-19? What might be new ways of engaging internationally if we are not physically able to travel in the ways we did before COVID-19? And how are we becoming creative with our dance education within this time of online learning, teaching and researching, and what might this offer international tertiary dance education? Through an auto-narrative approach we share three experiences from these early days within a changing wold, where we reflect on our role and practices as dance educators and researchers navigating these times. Themes of innovation, motivation, cultural agendas, slow scholarship, online pedagogy, and virtual and corporeal mobility are identified and discussed in relation to the potential future(s) for international tertiary dance education in a COVID-19 world.